2021
DOI: 10.3389/fpls.2021.658321
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Root Architectural Traits in Lactuca and Their Roles in Increasing Phosphorus-Use-Efficiency in Response to Low Phosphorus Availability

Abstract: Low phosphorus (P) bioavailability in the soil and concerns over global P reserves have emphasized the need to cultivate plants that acquire and use P efficiently. Root architecture adaptation to low P can be variable depending on species or even genotypes. To assess the genetic variability of root architectural traits and their responses to low P in the Lactuca genus, we examined fourteen genotypes including wild species, ancient and commercial lettuce cultivars at low (LP, 0.1 mmol. L–1) and high P (HP, 1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…A higher root length and finer root systems in plants are often interpreted in terms of response to a high level of N [ 22 , 36 ]; in lettuce enhanced root length, density at high N is reported [ 34 , 37 ]. Controversial behaviour is recorded for phosphorus: P deficiency is found to promote [ 38 , 39 ] or reduce [ 40 ] root proliferation, depending on species, but often results in finer root systems (e.g., [ 41 , 42 ]). In lettuce under low P, Beroueg et al [ 40 ] reported a higher taproot growth with lower branching, although branch diameters were finer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher root length and finer root systems in plants are often interpreted in terms of response to a high level of N [ 22 , 36 ]; in lettuce enhanced root length, density at high N is reported [ 34 , 37 ]. Controversial behaviour is recorded for phosphorus: P deficiency is found to promote [ 38 , 39 ] or reduce [ 40 ] root proliferation, depending on species, but often results in finer root systems (e.g., [ 41 , 42 ]). In lettuce under low P, Beroueg et al [ 40 ] reported a higher taproot growth with lower branching, although branch diameters were finer.…”
Section: Resultsmentioning
confidence: 99%
“…Controversial behaviour is recorded for phosphorus: P deficiency is found to promote [ 38 , 39 ] or reduce [ 40 ] root proliferation, depending on species, but often results in finer root systems (e.g., [ 41 , 42 ]). In lettuce under low P, Beroueg et al [ 40 ] reported a higher taproot growth with lower branching, although branch diameters were finer.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Beroueg et al. (2021) showed that low P stress inhibited primary root length and reduced lateral root number in 14 Lactua genotypes, while the degree of reduction varied among genotypes. P stress resulting from low P supply in soil reduced lateral root density in rice (Vejchasarn et al., 2016) and common bean (Borch et al., 1999).…”
Section: Discussionmentioning
confidence: 96%
“…There are also differences in PUE among cultivars of crop plants in the field ( Horst et al., 1993 ; Ciarelli et al., 1998 ; Rose et al., 2007 ; Powers et al., 2020 ; Beroueg et al., 2021 ). Differences in root architecture is a major contributor to this variability, with some cultivars more capable of increasing absorptive surface area under low P conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in root architecture is a major contributor to this variability, with some cultivars more capable of increasing absorptive surface area under low P conditions. ( Shenoy and Kalagudi, 2005 ; Beroueg et al., 2021 ). Cultivars can also vary in their ability to modify the rhizosphere by releasing organic acids and increasing the solubility of P in calcareous soils ( Shenoy and Kalagudi, 2005 ), but this is not typically beneficial in controlled environment agriculture where adequate fertilizer is continuously supplied and substrate pH is tightly controlled.…”
Section: Discussionmentioning
confidence: 99%